2018
DOI: 10.1021/acs.iecr.8b02211
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Characterization and Quantification Tools for Microbiologically Influenced Corrosion in the Oil and Gas Industry: Current and Future Trends

Abstract: This review evaluates the analytical methods used for detecting microbiologically influenced corrosion (MIC), which is an aggressive microbiota-facilitated degradation of engineering materials, and discusses their advantages and limitations. The challenges presented by the lack of a comprehensive mechanistic understanding on MIC detection, which include the need to use a combined array of morphological, chemical, electrochemical, and biological characterization for MIC detection, are thoroughly discussed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 297 publications
(529 reference statements)
0
12
0
Order By: Relevance
“…A field-emission gun environmental scanning electron microscope , was utilized to study the compositional features of the samples. The sample was analyzed using a Quanta 400 ESEM at 20 kV and 10 mm working distance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A field-emission gun environmental scanning electron microscope , was utilized to study the compositional features of the samples. The sample was analyzed using a Quanta 400 ESEM at 20 kV and 10 mm working distance.…”
Section: Methodsmentioning
confidence: 99%
“…Kannan et al 1 reviewed the analytical methods used for detecting microbiologically influenced corrosion (MIC) in the oil and gas industry and used a combination of morphological, compositional, electrochemical, and biological analyses of 77 studies on MIC. They showed that the microbiological assay techniques (e.g., metagenomics and metabolomics techniques) provide a rapid tool to evaluate MIC of corrosion deposits from refineries and gas plants.…”
Section: Introductionmentioning
confidence: 99%
“…There are various methods for testing the presence of microorganisms in samples suspected of MIC. The microscopy method is generally used for determining the overall numbers of microorganisms using a small amount of sample [37]. qPCR method is a molecular microbiological method (MMM) to enumerate microorganisms by amplifying the genetic sequences [38].…”
Section: Specific Detection Of B Carboniphilus In Bacterial Mixture and Biofilmmentioning
confidence: 99%
“…In oil fields, systems containing water are prone to uncontrolled microbial growth, which may trigger serious problems. Uncontrolled microbial activity can increase oil contamination, microbially induced corrosion, biofouling and the generation of dangerous metabolic byproducts, such as hydrogen sulfide (H 2 S), known as biosouring 1 , 2 .…”
Section: Introductionmentioning
confidence: 99%